The Effect of Work Motivation, Compensation and Work Environment on Job Satisfaction of State Polytechnic Employees Creative Media - Zackharia Rialmi; Hesti Prasetiya Ningrum; Nurmatias (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
The purpose of this study was to determine the effect of work motivation, compensation and work environment on job satisfaction of the employees of the Jakarta Creative Media State Polytechnic. The data used is quantitative data with a population of 258 and a sample of 115 responses. This research hypothesis was tested using Multiple Linier Regression Analysis Method with SPSS software program and with a significant level of 5%. The results obtained from this study are (1) there is a significant influence between work motivation and job satisfaction, (2) there is a significant influence between compensation and job satisfaction, (3) there is a significant influence between work environment and job satisfaction, and (4) there is a significant influence between motivation, compensation and work environment simultaneously or together on job satisfaction. In this study, because the Covid-19 pandemic has limitations, it is difficult for researchers to find references directly, and it is also difficult for researchers to distribute questionnaires directly. This research provides ideas that can considered by Jakarta Creative Media State Polytechnic in solving HR problems related to these variables, as well as assisting the learning process and application of science especially HR management science.